Pengaruh supervisi kepala sekolah, motivasi kerja oleh kepala sekolah dan disiplin kerja kepala sekolah terhadap kinerja guru SMK negeri bidang studi keahlian teknologi dan rekayasa di kelompok kerja Bantul Barat tahun ajaran 2013/2014 - Langgeng Sihana (Universitas Sarjanawiyata Tamansiswa, 2015)
This research aims to know (1) The influence of principal supervision, work motivation by Principal and principal discipline on the performance of technology and engineer vocational school teacher at the public vocational high school in western Bantul in 2013/2014. (2) The influence of principal supervision on the performance of technology and engineer vocational school teacher at the public vocational high school in western Bantul in 2013/2014. (3) The influence of work motivation by the principal on the performance of technology and engineer vocational school teacher at a public vocational high school in western Bantul in 2013/2014. (4) The influence of principal discipline on the performance of technology and engineer vocational school teacher at a public vocational high school in western Bantul in 2013/2014. The population of this research was 160 teachers of the vocational high school teacher at technology and engineer competence in western Bantul in 2013 / 2014 such as SMK N 1 Sedayu, SMK N 1 Pandak, SMK N 1 Sanden. The sampling of this research used proportional random sampling technique of 110 teachers. Data was collected using questionnaire which has been tried out to 30 teachers and has fulfilled the validity requirement with Pearson correlation technique and the reliability requirement with alpha Cronbach technique. The technique of data analysis was used descriptive analysis multiple regression and the partial correlation was started by analysis pre-requirement test that was multicollinearity, linearity and normality test. The result of research analysis shows that the teacher performance is at the high category, principal supervision is at the high category, work motivation by the principal is at the high category, principal discipline is at the high category. The result of multiple regression analysis shows 1) There is the influence of principal supervision, work motivation by the principal, and principal discipline on the performance of technology and engineer vocational school teacher at a public vocational high school in western Bantul in 2013/ 2014. It means that the higher principal supervision, work motivation by the principal and principal discipline will make the teacher performance is higher too. The result of partial correlation analysis shows that (2) There is a positive influence which is significant of principal supervision on the performance of the teacher. It means that higher principal supervision will make the teacher performance is higher too. 3) There is a positive influence which is significant of work motivation by the principal on the performance of the teacher. It means that higher work motivation by the principal will make the teacher performance is higher too. 4) There is a positive influence which is significant of principal work discipline on the performance of the teacher. It means that higher principal work discipline will make the teacher performance is higher too.